Mediators of change in healthcare organisations subject to external assessment: a systematic review with narrative synthesis. Issue 8 (30th August 2020) - Hovlid, Einar; Braut, Geir Sverre; Hannisdal, Einar; Walshe, Kieran; Bukve, Oddbjørn; Flottorp, Signe; Stensland, Per; Frich, Jan C
Abstract : Objectives: External inspections are widely used to improve the quality of care. The effects of inspections remain unclear and little is known about how they may work. We conducted a narrative synthesis of research literature to identify mediators of change in healthcare organisations subject to external inspections. Methods: We performed a literature search (1980–January 2020) to identify empirical studies addressing change in healthcare organisations subject to external inspection. Guided by the Consolidated Framework for Implementation Research, we performed a narrative synthesis to identify mediators of change. Results: We included 95 studies. Accreditation was the most frequent type of inspection (n=68), followed by statutory inspections (n=19), and external peer review (n=9). Our findings suggest that the regulatory context in which the inspections take place affect how they are acted on by those being inspected. The way inspections are conducted seem to be critical for how the inspection findings are perceived and followed up. Inspections can engage and involve staff, facilitate leader engagement, improve communication and enable the creation of new networks for reflection on clinical practice. Inspections can contribute to creating an awareness of the inspected organisation's current practice and performance gaps, and a commitment to change. Moreover, they can contribute to facilitating the planning and implementation of change, as well as self-evaluation and the use of data to evaluate performance. Conclusions: External inspections can affect different mediators of organisational change. The way and to what extent they do depend on a range of factors related to the outer setting, the way inspections are conducted and how they are perceived and acted on by the inspected organisation. To improve the quality of care, the organisational change processes need to involve and impact the way care is delivered to the patients.